Health-related quality of life of long-term advanced melanoma survivors treated with anti-CTLA-4 immune checkpoint inhibition compared to matched controls. (2nd January 2021) - Boekhout, A. H.; Rogiers, A.; Jozwiak, K.; Boers-Sonderen, M. J.; van den Eertwegh, A. J.; Hospers, G. A.; de Groot, J. W. B.; Aarts, M. J. B.; Kapiteijn, E.; ten Tije, A. J.; Piersma, D.; Vreugdenhil, G.; et al.
Abstract: Background: Checkpoint inhibitors have changed overall survival for patients with advanced melanoma. However, there is a lack of data on health-related quality of life (HRQoL) of long-term advanced melanoma survivors, years after treatment. Therefore, we evaluated HRQoL in long-term advanced melanoma survivors and compared the study outcomes with matched controls without cancer. Material and methods: Ipilimumab-treated advanced melanoma survivors without evidence of disease and without subsequent systemic therapy for a minimum of two years following last administration of ipilimumab were eligible for this study. The European Organization for Research and Treatment of Cancer quality of life questionnaire Core 30 (EORTC QLQ-C30), the Multidimensional Fatigue Inventory (MFI), the Hospital Anxiety and Depression Scale (HADS), and the Functional Assessment of Cancer Therapy-Melanoma questionnaire (FACT-M) were administered. Controls were individually matched for age, gender, and educational status. Outcomes of survivors and controls were compared using generalized estimating equations, and differences were interpreted as clinically relevant according to published guidelines. Results: A total of 89 survivors and 265 controls were analyzed in this study. After a median follow-up of 39 (range, 17–121) months, survivors scored significantly lower on physical (83.7 vs . 89.8, difference (diff) = −5.80, p =.005), role (83.5 vs. 90, diff = −5.97, p =.02), cognitive (83.7 vs. 91.9, diff = −8.05, p =.001), and social functioning (86.5 vs. 95.1, diff = −8.49, p = <.001) and had a higher symptom burden of fatigue (23.0 vs. 15.5, diff = 7.48, p =.004), dyspnea (13.3 vs. 6.7, diff = 6.47 p =.02), diarrhea (7.9 vs. 4.0, diff = 3.78, p =.04), and financial impact (10.5 vs. 2.5, diff = 8.07, p =.001) than matched controls. Group differences were indicated as clinically relevant. Discussion: Compared to matched controls, long-term advanced melanoma survivors had overall worse functioning scores, more physical symptoms, and financial difficulties. These data may contribute to the development of appropriate survivorship care.